Penegakan Hukum Terhadap Tindak Pidana Narkotika yang Dilakukan Oleh Anak Dibawah Umur di Bandar Lampung - Noviyana Hadiyati; Zainudin Hasan; Fayza Rizki Vianisya; Febby Cantika Firdaus (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2023)
Narcotics misuse and distribution have become so pervasive that everyone is now a victim. This study aims to "identify, clarify, and analyze the enforcement of laws against juvenile offenders of drug abuse in the Bandar Lampung area. It also examines the factors that contribute to juvenile offenders of drug abuse." With the normative juridical approach research was the methodology adopted for this analysis. Deductive reasoning techniques are employed in conjunction with normative legal research as the approach method for this article. The study's findings indicate that legal substances, legal institutions, legal environments, and legal cultures all have an impact on children's decisions to abuse drugs. The child's internal factors are the most significant ones. It has been successful to utilize law enforcement to stop those who abuse drugs on minors. It is the responsibility of parents to properly educate their children so that they are not susceptible to peer pressure to break the law.